Pengembangan Media Pembelajaran Interaktif Indonesiaku Kaya Budaya “INKAYA” Berbasis Unity untuk Meningkatkan Hasil Belajar IPAS Peserta Didik Kelas IV Sekolah Dasar - Yulia Cahyaningrum; Sri Sami Asih (Postgraduate, University of Mataram, 2025)
Based on pre-research data at SDN Tambangan 01 Semarang, the problem of the lack of interesting and IT-based learning media was found. This study aims to develop, assess the feasibility, and test the effectiveness of interactive learning media Inkaya based on Unity in the subject of science for grade IV. This type of research is Research and Development (R&D) with the Borg & Gall model involving 10 steps. The study population consisted of 28 grade IV students. Data collection techniques include tests, questionnaires, observations, interviews, and documentation, as well as data analysis using normality tests, t-tests, and N-gain tests. The results of the study showed that the Inkaya learning media based on Unity was feasible to use with a feasibility of 90% for presentation by media experts and feasibility of content by material experts. This media has also proven effective in improving student learning outcomes with a t-test value of 0.000 (significant) and an N-gain of 0.656 (moderate criteria). In conclusion, the Inkaya learning media based on Unity is effective and feasible to use in learning science for the material of Indonesian cultural wealth.